In This Together? Exploring Moderating and Mediating Effects of Shared Racal Fate on the Predictive Role of Racial Socialization and Discrimination on Black Activism. (May 2022) - Ajayi, Alex A.; Grier-Reed, Tabitha; Houseworth, James
This study examined the predictive role of reported racial socialization (i.e., preparation for bias and promotion of mistrust), racial discrimination, and shared racial fate on sociopolitical activism in a sample of 353 Black Americans. In addition, we examined the moderating and mediating role of shared racial fate as a variable by which the other contextual factors predict sociopolitical activism. Results from multiple regression analyses indicated that preparation for bias and racial discrimination were the only unique predictors of sociopolitical activism. Results also indicated that shared racial fate significantly moderated the relationship between reported racial discrimination and sociopolitical activism. Finally, shared racial fate significantly mediated the relationship between promotion of mistrust and sociopolitical activism. These findings are timely as we are at a critical point in U.S. history where there are widespread calls for social justice. We provide insight into factors that may contribute to sociopolitical engagement. Implications for culturally responsive pedagogy, curricula, and interventions are discussed.